PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN PROPERTI DI BURSA EFEK INDONESIA - Mardiana, Ferisca Tri; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to examine the influence of the financial performance to the stock return. The influence of financial performance is measured by financial ratios Liquidity ratio (Current Ratio), Profitability ratio (Return On Asset), Solvency ratio (Debt to Equity Ratio), and Activity ratio (Total Asset Turn Over) as the independent variable to the Stock Return as the dependent variable through the annual financial statements which have been prepared by property companies which are listed in Indonesia Stock Exchange. The population has been obtained by using purposive sampling method. The samples are property companies which are listed in Indonesia Stock Exchange (IDX) in 2013-2015 periods and based on the predetermined criteria then 23 property companies have been obtained as samples. The analysis method has been carried out by using multiple linear regression analysis and the SPSS (Statistical Product and Service Solution). The multiple regression analysis has been performed after the classic assumption test. The result of the hypothesis test indicates that Return on Asset and Total Asset Turn Over give significant influence to the stock return with the regression coefficient of Return on Assets is 0.323 and the regression coefficient of Total Asset Turn Over is 0.195. The significance level is 0.043 for both variables which give influence. Meanwhile, Current Ratio and Debt to Equity Ratio does not give any significant influence on Stock Return.Keywords: liquidity, profitability, solvency, activity, stock returns.